(untitled) (Journal of Education and Development, 2024)
Parental figures provide significant guidance in their children’s behavior to facilitate positive moral development. However, little is known about the moral implications of parental practices and its association with cyberbullying among emerging adults. The present study explored the potential mediating role of shame- and guilt-proneness in the association between parental practices and moral disengagement, and subsequently, the associations with cyberbullying behavior. Participants included postsecondary school students in Canada (N = 449; M = 21.85). age Results from structural equation modeling revealed that guilt-proneness was a significant partial mediator between perceived psychological control and moral disengagement, which, in turn, was associated with cyberbullying perpetration. Overall, this study highlights the implications of social-emotional contexts beyond adolescence, especially its associations with moral and aggression outcomes among emerging adults.